Purple Yam Extract (Dioscorea Alata L.) As Adjuvant Antihipertension Medicine for Postpartum Hipertension - Dina Hanifa; Suharyo Hadisaputro; Supriyana Supriyana; Bedjo Santoso (Universitas STRADA Indonesia, 2020)
One third of women who have hypertension in pregnancy will continue to have high blood pressure during the postpartum period. Potential adjuvant pharmacological therapy is needed, one of them is purple yam extract which contains flavonoids and dioscorin. This type of research is a quasi experiment. The research respondents consisted of 16 people treated with purple yam extract 320 mg/day and nifedipine 10 mg/day and 16 people were given nifedipin 10 mg/day for 14 days. The results of the study were the systolic of the intervention group decreased by 28.12 mmHg and the control group decreased by 8.94 mmHg with a p-value of 0,000. The diastolic of the intervention group decreased by 18.43 mmHg and the control group decreased by 3.75 mmHg with a p-value of 0,000. The conclusion of this study is purple yam extract has the potential as an alternative therapy to reduce blood pressure in postpartum hypertension.